Pengaruh Rebusan Daun Kersen Terhadap Penurunan Kadar Glukosa Darah Pada Penderita Diabetes Mellitus Tipe 2 - Sri Enawati; Nurista Nurista; Cemy Nur Fitria; Sri Handayani; Dwi Yuningsih (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2021)
Diabetes mellitus is a metabolic disorder caused by the pancreas not being able to produce enough insulin. Kersen leaves have saponin and flavanoid compounds that can inhibit the absorption of sugar from the intestine. Purpose: This study aims to determine whether there is an effect of cherry leaf cooking water on reducing blood sugar levels. Research Methods: The method used in this study was a quasi-experimental one group pretest-posttest design. The sampling technique was carried out by purposive sampling with data analysis carried out using a paired sample t-test. The research sample was diabetes mellitus sufferers at the Griya Husada 4 Karanganyar Clinic as many as 22 respondents. Given once a day for 6 days of administration. Results: It was found that the average decrease in fasting blood sugar levels before being given treatment was 156.00 mg/dl and the average after being given treatment was 120.67 mg/dl with a decrease in blood sugar levels of 35.33 mg/dl while for respondents Those who were not fasting obtained an average result before being given treatment was 175.90 mg/dl and after being given was 130.30 mg/dl. In respondents who were not fasting, it was seen that there was a decrease of 45.60 mg/dl. The significance value (p-value) is 0.000 (<0.005). Conclusion: There is an effect of cherry leaf cooking water on decreasing blood sugar levels in people with Diabetes Mellitus at Griya Husada Clinic 4 Karanganyar.